THE IMPORTANCE OF ADEQUATE PRE-ANALYTICAL MANAGEMENT FOR HISTOLOGICAL AND MOLECULAR EXAMINATION FOR DIAGNOSTIC PURPOSES - Krisna Murti; Nora Ramkita; Neti Neti; Aida Farida; Wresnindyatsih Wresnindyatsih; Aspitriani Aspitriani; Susilawati Susilawati (Conferences of Medical Sciences Dies Natalis, 2021)
Almost all Anatomic Pathology laboratories have experienced that tissue patient who comes to these laboratories without adequate fixation and causes complicated patient diagnosis. In addition, adequate fixation also makes advanced procedures such as immunohistochemical staining or DNA and RNA extraction difficult because protein, DNA, and RNA become damaged due to inadequate fixation. The fixation procedure should be the responsibility of the clinicians, specifically surgeons and team. If this procedure is not carried out appropriately resulting in damage to the tissue due to the natural process, namely autolysis, which the fixation procedure can prevent. This autolysis will damage the tissue. The laboratory process results are not optimal, complicating the evaluation of patient tissues, resulting in difficulty and delay of diagnosis. If further examination is needed, such as immunohistochemistry and other molecular examinations related to the extraction of DNA or RNA, the examination results will also be not optimal. Moreover, patient therapy becomes delayed or difficult. For this reason, we conducted extension activities for health workers, some of whom may be involved in a team of surgeons. Knowledge of pre-analytic procedures can improve the quality of pre-analytical handling, which will improve the quality of tissue andcytology specimens; hence, a precise and optimal diagnosis can be obtained. This will help the clinicians in determining the patient's therapy. Therefore, morbidity and mortality rates of patients can be reduced.